Disabilities caused by unstable mutations in Costa Rica - Cuenca, Patricia; Morales, Fernando; Castro, Isabel (Revista de Biología Tropical, 2004)
Myotonic dystrophy and fragile X syndrome are two genetically determined relatively common disabilities. Both are examples of a new type of mutation mechanism called unstable or dynamic mutations, triple repeats expansions or DNA amplification. Fragile X syndrome is recognized as the main cause of hereditary mental retardation and myotonic dystrophy is considered the most common muscular dystrophy of adults. This is a prospective non randomized study of clinically affected people, in order to confirm the diagnosis with molecular techniques (Southern blot and PCR) and to perform cascade screening of the rest of the family to offer them adequate genetic counseling. We were able to corroborate the initial diagnosis in most clinical cases of myotonic dystrophy, but in the cases of mental retardation more than half studies were negative for fragile X syndrome, stressing the difficulties encountered by medical practitioners to diagnose this syndrome. The reasons for this are several; probable the main culprit is the subtle and unspecific clinical picture affected individuals exhibit, particularly children before puberty. Cascade screening, genetic counseling and selective abortion are the only tools available to prevent these disabling diseases for the moment